2022
DOI: 10.1007/s10758-022-09624-8
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Competence of Higher Education Students as a Predictor of Academic Success

Abstract: The purpose of the present study is to analyze the digital competence of Higher Education students, as a function of their academic performance (have either repeated or a not previously), as well as to predict its significant predictors. For this, an ex-post factor and a sample of 17,301 students from Chile (Latin America) were utilized. A questionnaire composed of a total of 30 items, classified into five endogenous and exogenous dimensions through a causal model, adapted from the works of Gutiérrez-Castillo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This phenomenon implies that in order to solve educational problems, particularly in the context of improving the quality of human resources, action research must be conducted to find solutions to educational problems (Suherman et al, 2020;Supriadi et al, 2022;Supriyadi, J.Julia, et al, 2020). The researchers believe that this programme for the development of teachers' digital competencies must be highly promoted in the curriculum on campuses that produce educational candidates, considering that some research results show that this has not yet become a reality (Cabero-Almenara et al, 2022;Røkenes, 2016;Tømte, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon implies that in order to solve educational problems, particularly in the context of improving the quality of human resources, action research must be conducted to find solutions to educational problems (Suherman et al, 2020;Supriadi et al, 2022;Supriyadi, J.Julia, et al, 2020). The researchers believe that this programme for the development of teachers' digital competencies must be highly promoted in the curriculum on campuses that produce educational candidates, considering that some research results show that this has not yet become a reality (Cabero-Almenara et al, 2022;Røkenes, 2016;Tømte, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cabero‐Almenara et al. (2022) reported that students in Chile who did not repeat an academic year had a higher level of digital competence than those who repeated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2021) examined three dimensions of digital competence (i.e., technical skills, cognitive skills, and ethical knowledge), and Cabero‐Almenara et al. (2022) investigated six dimensions (i.e., technological literacy; search and treatment of information; critical thinking, problem solving, and decision making; communication and collaboration; digital citizenship; and creativity and innovation), they did not examine the specific relationships between these dimensions and student learning performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incorporating academic knowledge through educational videos on YouTube is an innovative methodological alternative to more traditional learning processes (Ríos Vázquez & Romero Tena, 2022), since “the incorporation of technology helps motivate students to learn” (Carstens et al, 2021, p. 106). The implementation of YouTube in the classroom requires moderate digital skills and competence on the part of teachers (Fernández del Río & Barreira Arias, 2017), with the teacher's level of digital competence influencing both the improvement of their students' digital skills and their academic performance (Cabero‐Almenara et al, 2023). However, the literature on digital learning has mainly focused on the content and format of learning, giving less relevance to learner behaviour (Noskova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%